Validation of Real-time Transthoracic 3D echocardiography in Children with Congenital Heart Disease - van den Bosch, Annemien E.; Harkel, Derk-Jan Ten; McGhie, Jackie S.; Roos-Hesselink, Jolien W.; Bogers, Ad J.J.C; Helbing, Wim A.; Meijboom, Folkert J. (SA Heart Journal, 2017)
Aims: Assessment of feasibility, accuracy and applicability in clinical practice of real-time three-dimensional echocardiography (RT-3DE) in children with congenital heart defects. Methods and results: From September 2004 to June 2005, 100 consecutive children (57 infants, 43 children > 1 year of age), who were scheduled for corrective intracardiac surgery, were enrolled in this study. RT-3DE was performed with Philips Sonos 7500 echo-system and off-line analysis with TomTec Echoview© software. Quantitative and qualitative assessments of the region of interest were performed on the 3D reconstruction, comparing these results with the anatomic findings and measurements performed during intracardiac surgery. Acquisition of RT-3DE datasets was feasible in 92 of the 100 (92%) patients and acquisition time was 6 ± 3 minutes. The overall quantitative analyses showed an excellent correlation (r < 0.90) between RT-3De and surgery. Also the qualitative analyses were accurate compared with surgical findings, in all patients in which RT-3DE was feasible. Conclusion: This study shows that RT-3DE can be used in the clinical practice for the assessment of intracardiac anatomy in children with congenital heart disease. The information derived from the 3D reconstructions can be taken into consideration in the preoperative planning and management regarding interventional or surgical therapy.